EFFECTIVE USE OF INFORMATION TECHNOLOGY IN TEACHING FOREIGN LANGUAGE SCIENCES - Jorayeva Yulduz Roziklovna (Western European Studies, 2024)
This article discusses the importance of using interactive methods and educational materials in teaching different foreign languages. In this, traditional teaching methods, which have always been used together with interactive methods, are compared.
Keywords: Method; technology; interactive methods